Analysis of location of key industries in Thailand - Boonjong Limudomporn; Pakorn Adulbhan; Sharif, M. N.; Woo, Wai-Ling; Government of Belgium (Bangkok : Asian Institute of Technology, 1974)
This study, is concerned with the decision problems of the management on plant location in Thailand. Emphasis is given to the key industries (as defined by ECAFE). An attempt is first made to find the location of plants in the key industries throughout the country on the provincial basis. Firms are classified in two categories -- Those which make (or have) the promotional privilege from the Thai Government, and those which do not. There seem to have two major patterns. One group of factories are located in the Bangkok area mainly along the banks of the Chao Phya River. They, in general, have a large percentage of the input materials imported in. The other major group is these factories whose important raw material(s) are mined or available in the up country area(s). be closed to the source of such materials. Their locations tend to As an attempt to describe how the management made their decisions in selecting the plant site, a questionnaire contained essential decision factors were sent to firms in the Bangkok area. The result are then analyzed. Since the industrial estate set up is receiving more attention as an important alternative for plant location, the existing industrial estate in Thailand -- The Banchan and Bangpoo Industrial Park --. The lack of incentives, communication facilities and the unknown roles of the estate made them not important in industrial location than they should be. Finally, a brief description is made of the ten relatively new investment zones scattering all over the country. The Board of Investment (BoI) is planning to give more attractive promotional privileges to firm locating their factories in the ten zones. This investment type of estate is hypothesized to be attractive to a significant number of potential investors.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1974
Keywords: Industries, Location of -- Thailand